An experimental study on the impact of two dimensional materials in waste disposal sites: What are the implications for engineered landﬁlls? (2016)
It is generally accepted that landﬁlled municipal solid waste develops a heterogeneous and anisotropic structure during placement, degradation and settlement. Flow and transport processes, in traditional and alternative landﬁlls, are strongly inﬂuenced by the type of structure developed. The presence of pref- erential ﬂow has gained research interest, given its impact on landﬁll processes. This paper describes an experimental investigation carried out on a specimen of degraded municipal solid waste. Preferential ﬂow was detected and caused by the specimen layered structure composed of two dimensional particles derived from less easily degradable materials such as plastics, textiles and paper which made up more than 50% of the specimen dry mass. The results suggest that two dimensional particles play a role in promoting preferential ﬂow because they modify ﬂow paths and increase the tortuosity. A high content of less easily degradable two dimensional materials suggests incompatibility with better management practices, seeking a more even distribution of ﬂuids to enhance degradation and faster stabilisation rates within engineered landﬁlls. Consequently, there is a need to re-think the types and quantities of materials that are restricted under current landﬁll policies.